Vascular access: choice and complications in European haemodialysis units. (24th May 2012) - Hayes, WN; Watson, AR
Abstract : Aims: European and US guidelines emphasise that permanent vascular access in the form of arteriovenous fistulae (AVF) or grafts (AVG) are preferable to central venous catheters (CVC) in paediatric patients on long-term haemodialysis. We report vascular access choice and complication rates in 13 European paediatric nephrology units. Methods: A survey of units participating in the European Paediatric Dialysis Working Group requesting data on type of vascular access, routine care and complications in patients on chronic haemodialysis between March 2010 and February 2011. Results: There were 111 patients in 13 participating centres with a median age of 14 years (0.25-20.2 years). Central venous catheters were used in 67 of 111 (60%) patients with 42 (38%) having an AVF and 2 patients (2%) having an AVG. Choice of vascular access was significantly related to patient age with mean age of patients with AVF/AVG 14.8 years compared to 10.6 years for patients with CVCs (p <0.0001). Routine CVC exit site care and catheter lock solution use differed between centres. CVC infections requiring intravenous antibiotics were reported at a rate of 1.9 and exit site infections at a rate of 1.8 episodes/1000 catheter days. Overall infective complications necessitating CVC change occurred at a rate of 0.9 episodes/1000 catheter days. No infective complications were reported in patients with AVF/AVG access. The rate of CVC infections requiring intravenous antibiotics was significantly lower in patients in whom CVC exit sites were cleaned weekly as opposed to every dialysis session (relative risk with every session cleaning versus weekly cleaning 2.58 [95% confidence interval (CI) 1.17-5.69]). Catheter malfunction (inadequate blood flow) was a more prevalent complication necessitating 22.4 thrombolytic interventions/1000 catheter days and 2.1 CVC changes/1000 catheter days. Conclusions: CVCs remain the predominant choice of vascular access in Europe despite problems of malfunction and infection. AVF/AVG were predominantly used in adolescents without reported complications. More regular exit site cleaning may predispose to CVC infection but this observation requires prospective evaluation.